Online Training in Religion – Mission Possible - Kyuchukova, Mirela (Forum Theologicum Sardicense, 2025)
Online learning has created a new pedagogical environment for all subjects, including religion. This change was implemented without a transition period and tested all participants in the educational process. The situation necessitates a reevaluation of current teaching standards and a reconsideration of the roles of teachers, students, and parents. Religious education in Bulgarian public schools has clear goals and objectives. Therefore, it is crucial to identify the appropriate methodology to achieve these objectives in the context of online learning.